The Dutch road to a high level of cycling safety. (February 2017) - Schepers, P.; Twisk, D.; Fishman, E.; Fyhri, A.; Jensen, A.
Abstract: Many governments attempt to improve cycling safety to reduce the number of bicycle crashes and encourage cycling. The Netherlands is a world leader in bicycle use and safety. This paper explores how the Netherlands achieved an 80% reduction in the number of cyclists killed (predominantly bicycle–motor vehicle crashes) per billion bicycle kilometres over a thirty year period. Factors found to contribute to this improvement include the establishment of a road hierarchy with large traffic-calmed areas where through traffic is kept out. A heavily used freeway network shifts motor vehicles from streets with high cycling levels. This reduces exposure to high-speed motor vehicles. Separated bicycle paths and intersection treatments decrease the likelihood of bicycle–motor vehicle crashes. The high amount of bicycle use increases safety as a higher bicycle modal share corresponds with a lower share of driving and greater awareness of cyclists among drivers. Low cycling speed was also found to contribute to the high level of cycling safety in the Netherlands.